ONE-YEAR PROSPECTIVE STUDY OF PATTERNS OF HOMICAL DEATHS- AN AUTOPSY BASED STUDY - BASRA, SUNNY; SINGH, JASPINDER PRATAP SINGH (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: The aim of the study was to observe the profiling of the homicidal cases for 1 year. Methods: The present study was a prospective 1-year study of all autopsies alleged to be homicide under 302 Indian Penal Code, performed in the department of forensic medicine and toxicology at Government Medical College, Amritsar, Punjab, India, from January 01, 2021 to December 31, 2021, (1-year period) after taking permission from the institutional ethical committee. Results: The majority of cases reported were in the age group of 20–49 years, with 24 (61.5%) cases, followed by the age group of 40–59 years, which had 13 (33.3%) cases. 37 (94.9%) cases were males, followed by females 02 (5.1%).The male-to-female sex ratio is 18.5:1; 30 (76.9%) were married, while 09 (23.1%) were unmarried. The deaceased had Sikh religion in 24 (61.6%) cases, followed by Hindus in 11 (28.2%) cases; 26 (66.7%) belonged to the rural area, while 13 (33.3%) belonged to the urban area. The majority of cases where only a sharp weapon was used were 16 (41%), followed by both blunt and sharp in 14 (35.9%) cases, and blunt only in 06 (15.4%). Firearms were used in 03 (7.7%) cases. Conclusion: Based on the aforementioned observations, we believe there is a pressing need to address issues concerning youth, given their frequent involvement in such crimes. Additionally, enforcing strict nighttime surveillance and rigorously implementing laws against individuals in possession of dangerous weapons can contribute significantly to reducing such crimes.